The Case against Carbon Prices - Patt, Anthony; Lilliestam, Johan (Joule, 2018)
Professor Dr. Anthony Patt is head of the Climate Policy Group in the Department of Environmental Systems Science at ETH Zürich, Switzerland. His research focus is on technological pathways and public policies for climate change mitigation and adaptation. He is a Coordinating Lead Author in Working Group III of the Intergovernmental Panel on Climate Change. He obtained his PhD at Harvard University's Kennedy School of Government. He is the author of “Transforming Energy: Solving Climate Change with Technology Policy” (Cambridge University Press, 2015).[Figure presented] Professor Dr. Johan Lilliestam is head of the Renewable Energy Policy Group in the Department of Environmental Systems Science at ETH Zürich, Switzerland. His research focus is policies and strategies for a transition to a completely renewable energy system, including the effects of interactions between different energy policies. He obtained his PhD at the Central European University in Budapest, Hungary. Before joining the ETH, he worked at the Potsdam Institute for Climate Impact Research (PIK) in Potsdam, Germany, and the International Institute for Applied Systems Analysis (IIASA) in Laxenburg, Austria. He currently holds a grant from the European Research Council for his work on policy interactions.[Figure presented]
CRIS-Team Scopus Importer:2023-06-14